The Recombinant Bacille Calmette–Guérin Vaccine VPM1002: Ready for Clinical Efficacy Testing - Nieuwenhuizen, Natalie E.; Kulkarni, Prasad S.; Shaligram, Umesh; Cotton, Mark F.; Rentsch, Cyrill A.; Eisele, Bernd; Grode, Leander; Kaufmann, Stefan H. E. (Frontiers in Immunology, 2017)
The only licensed vaccine against tuberculosis (TB), Bacille Calmette-Guérin (BCG), protects against severe extra pulmonary forms of TB but is virtually ineffective against the most prevalent form of the disease, pulmonary TB. BCG was genetically modified at the Max Planck Institute for Infection Biology to improve its immunogenicity by replacing the urease C encoding gene with the listeriolysin encoding gene from Listeria monocytogenes. Listeriolysin perturbates the phagosomal membrane at acidic pH. Urease C is involved in neutralization of the phagosome harboring BCG. Its depletion allows for rapid phagosome acidification and promotes phagolysosome fusion. As a result, BCGΔureC::hly (VPM1002) promotes apoptosis and autophagy and facilitates release of mycobacterial antigens into the cytosol. In pre-clinical studies, VPM1002 has been far more efficacious and safer than BCG. The vaccine was licensed to Vakzine Projekt Management and later sublicensed to the Serum Institute of India Pvt. Ltd., the largest vaccine producer in the world. The vaccine has passed phase I clinical trials in Germany and South Africa, demonstrating its safety and immunogenicity in young adults. It was also successfully tested in a phase IIa randomized clinical trial in healthy South African newborns, and is currently undergoing a phase IIb study in HIV exposed and unexposed newborns. A phase II/III clinical trial will commence in India in 2017 to assess efficacy against recurrence of TB. The target indications for VPM1002 are newborn immunization to prevent TB as well as post-exposure immunization in adults to prevent TB recurrence. In addition, a Phase I trial in non-muscle invasive bladder cancer patients has been completed, and phase II trials are ongoing. This review describes the development of VPM1002 from the drawing board to its clinical assessment.